Study on the socio-economic conditions of the fishermen in Teknaf (Research in Agriculture Livestock and Fisheries, 2015)
Study was conducted on the socio-economic conditions of the fishermen in Teknaf to evaluate fishermen livelihood and social status for a period of one year from March, 2014 to April, 2015. Data were collected in terms of income generation, age distribution, housing, literacy rate, health and sanitation facilities of the fishermen. Fishing was regarded as the major source of income of the traditional fishermen but occasionally they undertook a variety of non-fishery related activities, which constituted a substantial part of their annual income. Among 105 fishermen interviewed, 59.25% were below 30 years, 29.62% were between 30 and 39 years, and the remaining 11.11% were more than 40 years old, and their literacy level was 62.96% illiterate, 18.51% can write their names, 14.81% had received education up to primary level and 3.70% had received secondary education. Income distribution showed significant inequality between marginal and non-marginal fishermen from group fishing. The national and local NGO like BRAC, ASA provided credit only to the organized poor members to purchase fishing gears and boats but the amount of credit provided by the NGOs was insufficient and could not commensurate to the poor peoples actual need. The present study revealed that sanitary conditions of the fishermen were very poor that 25% fishermen have semi-constructed and 10% of the fishermen had no sanitary facilities. Most of the fishermen (65%) have un-constructed sanitary facilities. The present study suggested that there is a clear need to legalize fishing profession and their settlement as well as traditional fishing communities should be given priority in getting necessary supports from all concerns.Res. Agric., Livest. Fish.2(3): 483-489, December 2015